Inheritance Games : The Final Gambit - Book 3 - Barnes, Jennifer Lynn (New York ; Little, Brown and Company, 2022)
"Eighteen-year-old Avery Grambs is weeks away from inheriting the multibillion-dollar Hawthorne fortune, but first she'll have to survive a dangerous game against an old enemy looking for vengeance"--
Keywords: Inheritance and succession -- Juvenile fiction; Wealth -- Juvenile fiction; Puzzles -- Juvenile fiction; Family secrets -- Juvenile fiction; Secrecy -- Juvenile fiction; Families -- Juvenile fiction; Inheritance and succession -- Fiction; Wealth -- Fiction; Puzzles -- Fiction; Secrets -- Fiction; Families -- Fiction; Novels